Enhancing visual performance of hemianopia patients using overview window. (June 2020) - Zhao, Xi; Fujishiro, Issei; Go, Kentaro; Toyoura, Masahiro; Kashiwagi, Kenji; Mao, Xiaoyang
Highlights: Proposal of a computational glasses for visual field defect. Design of a whac-a-mole task for empirical performance evaluation. Optimal combinations of size, position, and opacity for overlaid window. Graphical abstract: Abstract: Visual field defect (VFD) is a type of ophthalmic disease that causes the loss of part of the patient's field of view (FoV). In this paper, we propose a method to enlarge the restricted FoV with an optical see-through head-mounted display (OST-HMD) equipped with a camera that captures an overview and overlays it on the persisting FoV. Because the overview window occludes the real background scene, it is important to create a balance between the augmented contextual information and the unscreened local information. We recruited twelve participants and conducted an experiment to seek the best size, position, and opacity for the overview window through a Whac-A-Mole task (a touchscreen game). We found that the performance was better when the overview window was of medium size (FoV of 9.148 ∘  × 5.153 ∘, nearly one third of FoV of the used OST-HMD) and placed lower in the visual field. Either too large or too small a size decreases the performance. The performance increases with increased opacity. The obtained results can legitimate the default setting for the overview window.